Obstructive Sleep Apnea Syndrome. Part III. Therapy - R. Foltán (Czech Dental Chamber, 2005)
OSAS therapy can have the form of either conservative or surgical treatment. The conservative therapy, applied in mild OSAS, consists in reducing the patient's wieght, introducing the correct sleep hygiene and using mandibular protractors. When treating cases of severe OSAS, we can apply Continuous Positive Airway Pressure - CPAP device overnight. If the conservative therapy does not result in improved sleep ventilation or if it is badly tolerated by the patient, we can use surgical treatment. We are providing uvulo-palato-pharyngo-plasty, palatal flap, genioglossus advancement with hyoid bone suspension or hyoid myotomy and maxillomandibular advancement. The cooperation with a dentist is always desirable during individual surgical interventions and, indeed, it is often indispensable.